The Role of Waste Management in Achieving Sustainable Tourism Development in Mandalika, Lombok Tengah: A Review of Best Practices and Challenges - Latif, B Syarifuddin; Satiaji, Amirosa Ria; Demolinggo, Ramang H.; Asyari; Pratama, Reza Aditya (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2024)
The development of Mandalika, Lombok Tengah, as a sustainable tourism destination, is crucial for the region's economic growth and environmental conservation. However, the increasing tourists pose significant challenges, particularly regarding waste management. This review aims to examine the role of waste management in achieving sustainable tourism development in Mandalika, Lombok Tengah, by identifying best practices and challenges. The study reveals that effective waste management is essential to mitigate the negative impacts of tourism on the environment and local communities. Adopting renewable energy sources, such as biogas technology, can convert food waste into energy, providing a sustainable solution to waste management. Moreover, implementing solid waste management (SWM) alternatives, including on-site facilities and incineration, can reduce the amount of waste diverted to landfills. The study also highlights the importance of involving local communities in waste management efforts and promoting sustainable tourism practices among tourists. However, challenges persist, including adequate infrastructure, institutional capacity, and community engagement. This review provides insights into the critical role of waste management in achieving sustainable tourism development in Mandalika, Lombok Tengah. It recommends policymakers, stakeholders, and tourists to promote environmentally friendly and socially responsible tourism practices.